Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4236/ojemd.2015.51001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soy Nuts on Glycemic Control, Lipid Profile and Insulin-Resistance in Type 2 Diabetic Patients

Abstract: Background: Type 2 diabetes has a high prevalence and a growing trend. The use of a proper diet treatment is one of the therapeutic approaches of patients. The use of the soy has shown the effective results in glycemic control of patients with type 2 diabetes; however, data are paradoxical. The present study aimed to examine the effectiveness of soy nuts on glycemic control, blood pressure and lipid profile and insulin-resistance of the diabetic patients. Methods: In this case-control study 69 type 2 diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Fiber content (Lu et al, 2013) and high protein (Ahmed et al, 2010) in Okara has the ability to reduce the FBG level. These fibers contain bioactive components with high viscosity, these components can directly slow the discharge of the stomach and absorption of glucose due to the hypoglycemic effect on Okara (Sedaghat et al, 2015). The mechanism of fiber to decrease in blood glucose levels is strongly influenced by the absorption of carbohydrates in the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber content (Lu et al, 2013) and high protein (Ahmed et al, 2010) in Okara has the ability to reduce the FBG level. These fibers contain bioactive components with high viscosity, these components can directly slow the discharge of the stomach and absorption of glucose due to the hypoglycemic effect on Okara (Sedaghat et al, 2015). The mechanism of fiber to decrease in blood glucose levels is strongly influenced by the absorption of carbohydrates in the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian yang dilaporkan oleh Sedaghat et al (2015), relawan DM-2 yang diberi intervensi kedelai sebanyak 30 g pada pagi dan sore selama 8 minggu menunjukkan penurunan GDP secara signifikan dari 165,50±51,00 mg/dL menjadi 148,20±49,00 mg/dL. Hasil GDP ini berbeda dengan hasil penelitian dimana nilai GDP relawan yang intervensi produk tidak menunjukkan penurunan signifikan dari 185,82±95,50 menjadi 143,09±58,93 mg/dL.…”
Section: Kadar Gula Darah Puasa (Gdp)unclassified
“…Hal ini terjadi diduga relawan yang diintervensi dengan produk tidak dikontrol pola diet selama masa intervensinya. Pada relawan kontrol, Sedaghat et al (2015), melaporkan terjadi peningkatan kadar GDP secara signifikan dari 161,70±41,20 mg/dL menjadi 167,50±42,30 mg/dL pada grup kontrol. Temuan ini juga berbeda dari temuan pada grup kontrol pada penelitian ini yang secara kontras tidak berbeda signifikan (dari 255,00±93,33 mg/dL menjadi 220,00±55,50 mg/dL).…”
Section: Kadar Gula Darah Puasa (Gdp)unclassified
“…The consumption of nuts has gained attention once it was demonstrated an inverse association of nut consumption with total and cause-specific mortality in healthy adults (mean age of 60 years) [77]. Also regarding nuts consumption, it has been recently demonstrated that the consumption of 60 grams per day of soy nuts in patients with T2DM for eight weeks was able to reduce fasting blood glucose, insulin concentration, as well as systolic and diastolic blood pressure [78].…”
Section: Dietary Interventionsmentioning
confidence: 99%